Physical Fitness and Exercise During the COVID-19 Pandemic: A Qualitative Enquiry - Kaur, Harleen; Singh, Tushar; Arya, Yogesh Kumar; Mittal, Shalini (Frontiers in Psychology, 2020)
The COVID-19 pandemic has brought this fast-moving world to a standstill. The impact of this pandemic is massive and the only strategy to curb its rapid spread is to follow social distancing. The imposed lockdown, resulting in the closure of business activities, public places, fitness and activity centers, and overall social life, has hampered many aspects of the lives of people including routine fitness activities of fitness freaks and has resulted in various psychological issues, and serious fitness and health concerns. In the present paper, the authors aimed at understanding the unique experiences of fitness freaks during the period of lockdown due to COVID-19 and to explore how alternate exercises and fitness activities at home helped them deal with psychological issues and physical health consequences. Semi-structured telephonic interviews were conducted with 22 adults who were regularly working out in the gym before Covid-19 pandemic’s lockdown but stayed at home during the nationwide lockdown. The analysis revealed that during the initial phase of the home confinement participants had the negative situational perception, lack of motivation for fitness exercise, showed psychological health concerns, and overdependence on social media for spending their free time. However, there was a gradual increase in positive self-perception and motivation to overcome their dependence on the gym and fitness equipment, and to continue fitness exercises at home. Participants also tended to play music as a tool while working out. The regular fitness workout at home during the lockdown greatly helped them to overcome psychological issues and fitness concerns.